Música de América : estudio preliminar y edición crítica - Wolkowicz, Vera (Investigaciones de la Biblioteca Nacional., 2012)
Compilation of pieces originally published from 1920 to 1922 in the journal Música de América, with introductory essay and critical notes in Spanish.